Public and Service Activity of the Ministry of Internal Affairs of Ukraine: Current Issues - O. V. Dzhafarova; O. O. Mozhovyi (Bulletin of Kharkiv National University of Internal Affairs)
The author has studied scientific concepts on the introduction of service-oriented activities of public administration authorities aimed at meeting the needs and interests of society through the provision of quality public services to the population, coordinated with long-term goals of society and state’s development.